Photovoltaic solar cell printing silver paste material and preparation method thereof
By adding lead oxide borosilicate glass and polypropylene glycol-modified silver powder to silver paste, the particle size and ratio of silver powder were controlled, the problem of silver powder agglomeration was solved, the dispersibility and welding strength of the silver paste were improved, and the welding quality and performance of photovoltaic cells were enhanced.
Patent Information
- Application Number
- CN202511112687.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-09
- Publication Date
- 2025-11-14
AI Technical Summary
In the printing process, silver powder tends to agglomerate in existing photovoltaic solar cell silver paste, leading to uneven solder joints and insufficient mechanical strength of the welded joints, which affects the performance stability of the battery module.
By adding components such as lead oxide borosilicate glass to silver paste, and using polypropylene glycol to modify dendritic and spherical silver powder, controlling the particle size and ratio of silver powder, and combining specific modification steps and solution concentration, a uniform conductive network is formed.
This achieves uniform dispersion of silver powder in silver paste, improves welding tensile strength and printing process stability, and enhances the welding reliability and overall performance of the battery cells.
Abstract
Description
Technical Field
[0001] This application relates to the field of silver paste preparation technology, and more specifically, to a printing silver paste material for photovoltaic solar cells and a method for preparing the same. Background Technology
[0002] Silver paste is a paste used to fabricate silver electrodes. It is formulated from silver or its compounds, flux, binder, and diluent. Based on the form of silver, it can be classified as oxide silver paste, carbonated silver paste, and molecular silver paste; based on the coating method, it can be classified as printing silver paste, spraying silver paste, etc. Currently, with the rapid development of the photovoltaic industry, low-temperature silver paste used in the manufacturing process of solar cells has become one of the key technologies. Due to the inherent characteristics of silver powder and the limitations of traditional formulation design, silver powder in current commercially available silver pastes is prone to agglomeration in the paste, which affects its uniformity during printing and the strength of solder joints, especially in the welding of solar cells with fine grid structures. Furthermore, insufficient curing reaction also restricts the mechanical strength of the weld joint, affecting the overall performance stability of the solar cell module. To overcome the problems of silver powder agglomeration and poor curing effect, the industry has explored the introduction of various additives, such as surfactants and coupling agents, in an attempt to enhance the dispersibility and bonding strength of silver powder. However, these methods either fail due to improper selection of additives or result in unstable paste viscosity due to excessive addition, affecting printability. Therefore, finding new formulations that can effectively improve the dispersibility of silver powder and significantly enhance the curing effect has become an urgent need in the industry. Summary of the Invention
[0003] To achieve high dispersion and high welding tensile strength in silver paste, this application provides a printing silver paste material for photovoltaic solar cells and its preparation method.
[0004] In a first aspect, this application provides a printing silver paste material for photovoltaic solar cells, comprising the following raw materials in parts by weight: 75-95 parts by weight of silver powder, 3-25 parts by weight of resin, 2-20 parts by weight of organic solvent, and 0.1-3 parts by weight of curing agent.
[0005] In one specific implementation, the silver paste material further includes the following raw materials in parts by weight: 3-8 parts lead borosilicate glass, 14-16 parts aluminum oxide, 2.0-2.2 parts boron trioxide, 0.5-0.7 parts cadmium oxide, 0.1-0.3 parts calcium oxide, 0.5-0.7 parts copper oxide, 4.3-4.5 parts phosphorus pentoxide, 5.1-5.3 parts platinum oxide, 2.4-2.6 parts silicon dioxide, and 0.7-0.9 parts zinc oxide.
[0006] By adopting the above preparation method, a certain mass of lead oxide borosilicate glass and other components are added to the silver paste. During the sintering process, the glass melts and wets the Ag / SiNx interface. Then, PbO and SiNx in the glass react and penetrate the antireflective film. During the penetration of SiNx, Pb and Ag form an alloy, and Ag is sintered in the liquid phase. Further, Ag dissolves in the glass material and diffuses towards the emitter surface. Near the silicon emitter, Ag ions are consumed and oxidize silicon to SiO2. + The silver particles pass through the molten glass and deposit onto the silicon surface, forming a sintering contact. Small Ag particles precipitate within the glass. During cooling, the solubility of Ag in the glass decreases, and nano-Ag deposits from within the glass frit. Kinetic constraints on grain growth during rapid cooling result in a high-density distribution of nanocrystalline silver in the glass interlayer. Through the combined effects of direct contact, tunneling, and percolation, a uniform and fully sintered silver layer is achieved.
[0007] In one specific embodiment, the silver powder comprises polypropylene glycol modified dendritic silver powder and polypropylene glycol modified spherical silver powder in a volume ratio of 1:(2.1-2.8).
[0008] By adopting the above preparation method, two different shapes of silver powder are modified with polypropylene glycol, which makes them better dispersed in silver paste and improves the bonding strength between silver powders. The resulting silver paste has better cohesion, more uniform printing process, and more reliable solder joints.
[0009] In one specific implementation, the average particle size of the dendritic silver powder is 1.0-3.0 μm, and the average particle size of the spherical silver powder is 200-800 nm.
[0010] By adopting the above preparation method, the particle size of dendritic silver powder and spherical silver powder are respectively limited, making them more suitable for the component settings of the silver paste system of this application, dispersing them more uniformly, and forming a more stable conductive network.
[0011] In one specific implementation, the nanospherical silver powder includes small spherical silver powder with an average particle size of 200-400 nm and large spherical silver powder with an average particle size of 500-800 nm, and the volume ratio of small spherical silver powder to large spherical silver powder is 2:(1.0-1.5).
[0012] By adopting the above preparation method, the spherical silver powder is limited to two sizes and two particle sizes. The smaller spherical silver powder can better fill the gaps in the silver paste, and at the same time, it is not easy to settle in the system, resulting in better performance of the silver paste.
[0013] In one specific implementation, the preparation steps of polypropylene glycol modified spherical silver powder include: adding spherical silver powder to an ethanol-polypropylene glycol mixed solution, sonicating, filtering, and drying to obtain polypropylene glycol modified spherical silver powder.
[0014] By adopting the above preparation method, the preparation steps are simple, the spherical silver powder is fully modified, the wetting performance is good, the compatibility in the system is better, and the resulting silver paste has greater welding pull strength.
[0015] In one specific implementation, the mass ratio of ethanol to polypropylene glycol in the ethanol-polypropylene glycol mixed solution added to the small spherical silver powder is 1:(2.8-3.0), and the mass ratio of ethanol to polypropylene glycol in the ethanol-polypropylene glycol mixed solution added to the large spherical silver powder is 1:(2.1-2.3).
[0016] By adopting the above preparation method, the concentration of the modified ethanol-polypropylene glycol mixed solution of large and small spherical silver powders is limited respectively, so that the number of surface active groups and surface energy of the prepared large and small spherical silver powders are more suitable for the silver paste system of this application, and the dispersion is more uniform and stable.
[0017] In one specific implementation, the average molecular weight of polypropylene glycol is 1800-2100.
[0018] In one specific implementation, the organic solvent includes dimethyl oxalate and the resin includes bisphenol A epoxy resin.
[0019] By adopting the above preparation method, limiting the average molecular weight of polypropylene glycol, the degree of modification, the number of surface active groups and viscosity of large and small spherical silver powders were further adjusted, and the types of organic solvents and resins were limited. The resulting silver powder is more suitable for the viscosity and other parameters of the silver paste system of this application, and the silver powder is more uniformly and stably distributed in the silver paste system.
[0020] Secondly, this application provides a method for preparing a photovoltaic solar cell printing silver paste material, comprising the following preparation steps: weighing raw materials according to weight parts, adding resin to an organic solvent, stirring at 60-85℃ until dissolved, cooling and adding curing agent and mixing evenly, then adding the remaining components and mixing evenly, grinding according to the gap between fast roller and medium roller: 70um, 40um, and the gap between medium roller and slow roller: 30um, 10um, and then vacuum degassing to obtain the photovoltaic solar cell printing silver paste material.
[0021] The above preparation method is simple, the components in the system are evenly and stably distributed, the silver powder is not easy to agglomerate in the paste, and the prepared silver paste is stable and reliable in the printing process and has high welding tensile strength.
[0022] In summary, this application has at least the following beneficial effects: This application adds a certain amount of resin, solvent, lead oxide borosilicate glass and other components to the silver paste material, so that the silver powder can melt the glass and wet the Ag / SiNx interface glass intermediate layer with high density of nanocrystalline silver. The resulting silver paste is uniformly and stably dispersed, has good compatibility and high welding tensile strength.
[0023] This application limits the shape, particle size, polypropylene glycol modification, and volume ratio of the silver powder, and further limits the modification steps and modification concentration, so that the number of surface active groups and surface energy of the silver powder are more suitable for the system of this application. This effectively suppresses the agglomeration of silver powder in the paste, greatly improves the dispersibility and wettability of the silver powder, and ensures the uniformity of the printing process and the reliability of the solder joints. Detailed Implementation
[0024] To further aid in understanding the technical solution of the present invention, several specific embodiments are provided to describe the technical solution of the present invention in more detail. All described embodiments are only some embodiments of the present invention, not all of them; embodiments can be combined with each other, and the same or similar concepts or processes may not be repeated in some embodiments. The following embodiments are further illustrations of the present invention, but the present invention is not limited thereto.
[0025] The raw materials used in the embodiments and preparation examples of this application are all conventional commercially available brands, or can be obtained according to conventional processes.
[0026] Preparation Example Preparation Example 1: Polypropylene Glycol Modified Dendritic Silver Powder Add 10g of dendritic silver powder to 100ml of a 1:2.0 volume ratio ethanol-polypropylene glycol mixed solution, sonicate at 300W for 10 minutes, filter, and dry to obtain polypropylene glycol modified dendritic silver powder.
[0027] In this preparation example, the average particle size of the dendritic silver powder is 2.0 μm, and the average molecular weight of the polypropylene glycol is 2000.
[0028] Preparation Example 2: Polypropylene Glycol Modified Large Spherical Silver Powder Add 10g of large spherical silver powder to 100ml of a 1:2.0 volume ratio ethanol-polypropylene glycol mixed solution, sonicate at 300W for 10 minutes, filter, and dry to obtain polypropylene glycol modified large spherical silver powder.
[0029] In this preparation example, the average particle size of the large spherical silver powder is 700 nm, and the average molecular weight of the polypropylene glycol is 2000.
[0030] Preparation Example 3: Polypropylene Glycol Modified Large Spherical Silver Powder Add 10g of large spherical silver powder to 100ml of a 1:2.2 volume ratio ethanol-polypropylene glycol mixed solution, sonicate at 300W for 10 minutes, filter, and dry to obtain polypropylene glycol modified large spherical silver powder.
[0031] In this preparation example, the average particle size of the large spherical silver powder is 700 nm, and the average molecular weight of the polypropylene glycol is 2000.
[0032] Preparation Example 4: Polypropylene Glycol Modified Microspherical Silver Powder Add 10g of small spherical silver powder to 100ml of a 1:2.2 volume ratio ethanol-polypropylene glycol mixed solution, sonicate at 300W for 10 minutes, filter, and dry to obtain polypropylene glycol modified small spherical silver powder.
[0033] In this preparation example, the average particle size of the small spherical silver powder is 300 nm, and the average molecular weight of the polypropylene glycol is 2000.
[0034] Preparation Example 5: Polypropylene Glycol Modified Microspherical Silver Powder Add 10g of small spherical silver powder to 100ml of a 1:2.9 volume ratio ethanol-polypropylene glycol mixed solution, sonicate at 300W for 10 minutes, filter, and dry to obtain polypropylene glycol modified small spherical silver powder.
[0035] In this preparation example, the average particle size of the small spherical silver powder is 300 nm, and the average molecular weight of the polypropylene glycol is 2000.
[0036] Preparation Example 6: Polypropylene Glycol Modified Microspherical Silver Powder Add 10g of small spherical silver powder to 100ml of a 1:2.2 volume ratio ethanol-polypropylene glycol mixed solution, sonicate at 300W for 10 minutes, filter, and dry to obtain polypropylene glycol modified small spherical silver powder.
[0037] In this preparation example, the average particle size of the small spherical silver powder is 300 nm, and the average molecular weight of the polypropylene glycol is 2500. Example
[0038] Example 1: This embodiment includes the following raw materials by weight: 75g of large spherical silver powder with an average particle size of 700nm, 3g of bisphenol A epoxy resin, 2g of dimethyl oxalate organic solvent, 3g of isocyanate curing agent, 3g of lead oxide borosilicate glass, 14g of aluminum oxide, 2.0g of boron trioxide, 0.5g of cadmium oxide, 0.3g of calcium oxide, 0.7g of copper oxide, 4.5g of phosphorus pentoxide, 5.3g of platinum oxide, 2.6g of silicon dioxide, and 0.9g of zinc oxide.
[0039] The process includes the following steps: weighing the raw materials by weight, adding the resin to the organic solvent, stirring at 70°C until dissolved, cooling to room temperature, adding the curing agent and mixing evenly, then adding the remaining components and mixing evenly, grinding with a fast roller-medium roller gap of 70µm and 40µm, and a medium roller-slow roller gap of 30µm and 10µm, and then vacuum degassing to obtain the photovoltaic solar cell printing silver paste material.
[0040] Example 2: The only difference between this example and Example 1 is that: The raw materials include the following quantities: 95g of large spherical silver powder with an average particle size of 700nm, 25g of bisphenol A epoxy resin, 20g of dimethyl oxalate organic solvent, 0.1g of isocyanate curing agent, 8g of lead oxide borosilicate glass, 16g of aluminum oxide, 2.0g of boron trioxide, 0.5g of cadmium oxide, 0.3g of calcium oxide, 0.7g of copper oxide, 4.5g of phosphorus pentoxide, 5.1g of platinum oxide, 2.4g of silicon dioxide, and 0.9g of zinc oxide.
[0041] Example 3: The only difference between this example and Example 1 is that: The raw materials include the following quantities: 90g of large spherical silver powder with an average particle size of 700nm, 15g of bisphenol A epoxy resin, 12g of dimethyl oxalate organic solvent, 2g of isocyanate curing agent, 6g of lead oxide borosilicate glass, 15g of aluminum oxide, 2.0g of boron trioxide, 0.5g of cadmium oxide, 0.3g of calcium oxide, 0.6g of copper oxide, 4.5g of phosphorus pentoxide, 5.1g of platinum oxide, 2.4g of silicon dioxide, and 0.9g of zinc oxide.
[0042] Example 4: The only difference between this example and Example 1 is that: The raw materials include the following quantities: 90g of polypropylene glycol modified dendritic silver powder prepared in Example 1, 15g of bisphenol A epoxy resin, 12g of dimethyl oxalate organic solvent, 2g of isocyanate curing agent, 6g of lead oxide borosilicate glass, 15g of aluminum oxide, 2.0g of boron trioxide, 0.5g of cadmium oxide, 0.3g of calcium oxide, 0.6g of copper oxide, 4.5g of phosphorus pentoxide, 5.1g of platinum oxide, 2.4g of silicon dioxide, and 0.9g of zinc oxide.
[0043] Example 5: The only difference between this example and Example 1 is that: The raw materials include the following quantities: 25g of polypropylene glycol modified dendritic silver powder prepared in Preparation Example 1, 65g of polypropylene glycol modified large spherical silver powder prepared in Preparation Example 2, 15g of bisphenol A epoxy resin, 12g of dimethyl oxalate organic solvent, 2g of isocyanate curing agent, 6g of lead oxide borosilicate glass, 15g of aluminum oxide, 2.0g of boron trioxide, 0.5g of cadmium oxide, 0.3g of calcium oxide, 0.6g of copper oxide, 4.5g of phosphorus pentoxide, 5.1g of platinum oxide, 2.4g of silicon dioxide, and 0.9g of zinc oxide.
[0044] Example 6: The only difference between this example and Example 1 is that: The raw materials include the following quantities: 25g of polypropylene glycol modified dendritic silver powder prepared in Preparation Example 1, 65g of polypropylene glycol modified large spherical silver powder prepared in Preparation Example 3, 15g of bisphenol A epoxy resin, 12g of dimethyl oxalate organic solvent, 2g of isocyanate curing agent, 6g of lead oxide borosilicate glass, 15g of aluminum oxide, 2.0g of boron trioxide, 0.5g of cadmium oxide, 0.3g of calcium oxide, 0.6g of copper oxide, 4.5g of phosphorus pentoxide, 5.1g of platinum oxide, 2.4g of silicon dioxide, and 0.9g of zinc oxide.
[0045] Example 7: The only difference between this example and Example 1 is that: The raw materials include the following quantities: 25g of polypropylene glycol modified dendritic silver powder obtained in Preparation Example 1, 25g of polypropylene glycol modified large spherical silver powder obtained in Preparation Example 3, 40g of polypropylene glycol modified small spherical silver powder obtained in Preparation Example 4, 15g of bisphenol A epoxy resin, 12g of dimethyl oxalate organic solvent, 2g of isocyanate curing agent, 6g of lead oxide borosilicate glass, 15g of aluminum oxide, 2.0g of boron trioxide, 0.5g of cadmium oxide, 0.3g of calcium oxide, 0.6g of copper oxide, 4.5g of phosphorus pentoxide, 5.1g of platinum oxide, 2.4g of silicon dioxide, and 0.9g of zinc oxide.
[0046] Example 8: The only difference between this example and Example 1 is that: The raw materials include the following quantities: 25g of polypropylene glycol modified dendritic silver powder prepared in Preparation Example 1, 25g of polypropylene glycol modified large spherical silver powder prepared in Preparation Example 3, 40g of polypropylene glycol modified small spherical silver powder prepared in Preparation Example 5, 15g of bisphenol A epoxy resin, 12g of dimethyl oxalate organic solvent, 2g of isocyanate curing agent, 6g of lead oxide borosilicate glass, 15g of aluminum oxide, 2.0g of boron trioxide, 0.5g of cadmium oxide, 0.3g of calcium oxide, 0.6g of copper oxide, 4.5g of phosphorus pentoxide, 5.1g of platinum oxide, 2.4g of silicon dioxide, and 0.9g of zinc oxide.
[0047] Example 9: The only difference between this example and Example 1 is that: The raw materials include the following quantities: 25g of polypropylene glycol modified dendritic silver powder prepared in Preparation Example 1, 25g of polypropylene glycol modified large spherical silver powder prepared in Preparation Example 3, 40g of polypropylene glycol modified small spherical silver powder prepared in Preparation Example 6, 15g of bisphenol A epoxy resin, 12g of dimethyl oxalate organic solvent, 2g of isocyanate curing agent, 6g of lead oxide borosilicate glass, 15g of aluminum oxide, 2.0g of boron trioxide, 0.5g of cadmium oxide, 0.3g of calcium oxide, 0.6g of copper oxide, 4.5g of phosphorus pentoxide, 5.1g of platinum oxide, 2.4g of silicon dioxide, and 0.9g of zinc oxide.
[0048] Example 10: The only difference between this example and Example 1 is that: The raw materials include the following quantities: 25g of polypropylene glycol modified dendritic silver powder prepared in Preparation Example 1, 25g of polypropylene glycol modified large spherical silver powder prepared in Preparation Example 3, 40g of polypropylene glycol modified small spherical silver powder prepared in Preparation Example 5, 15g of bisphenol A epoxy resin, 12g of divalent ester organic solvent, 2g of isocyanate curing agent, 6g of lead oxide borosilicate glass, 15g of aluminum oxide, 2.0g of boron trioxide, 0.5g of cadmium oxide, 0.3g of calcium oxide, 0.6g of copper oxide, 4.5g of phosphorus pentoxide, 5.1g of platinum oxide, 2.4g of silicon dioxide, and 0.9g of zinc oxide.
[0049] Comparative Example Comparative Example 1: This comparative example includes the following raw materials by weight: 110g of large spherical silver powder with an average particle size of 700nm, 3g of bisphenol A epoxy resin, 2g of dimethyl oxalate organic solvent, 3g of isocyanate curing agent, 3g of lead oxide borosilicate glass, 14g of aluminum oxide, 2.0g of boron trioxide, 0.5g of cadmium oxide, 0.3g of calcium oxide, 0.7g of copper oxide, 4.5g of phosphorus pentoxide, 5.3g of platinum oxide, 2.6g of silicon dioxide, and 0.9g of zinc oxide.
[0050] The process includes the following steps: weighing the raw materials by weight, adding the resin to the organic solvent, stirring at 70°C until dissolved, cooling to room temperature, adding the curing agent and mixing evenly, then adding the remaining components and mixing evenly, grinding with a fast roller-medium roller gap of 70µm and 40µm, and a medium roller-slow roller gap of 30µm and 10µm, and then vacuum degassing to obtain the photovoltaic solar cell printing silver paste material.
[0051] Performance testing The silver pastes prepared in the examples and comparative examples were screen printed sequentially, sintered at 350°C, and the cell efficiency and welding tensile strength were tested.
[0052] The test results are shown in Table 1.
[0053] Table 1 Welding tensile force / N Cell efficiency / % Example 1 0.9 0.203 Example 2 0.9 0.201 Example 3 1.1 0.206 Example 4 1.2 0.209 Example 5 1.4 0.213 Example 6 1.4 0.217 Example 7 1.5 0.227 Example 8 1.6 0.231 Example 9 1.5 0.220 Example 10 1.5 0.219 Comparative Example 1 0.7 0.191 In conjunction with Examples 1-3, Comparative Example 1, and Table 1, the silver paste material prepared in this application exhibits superior performance.
[0054] In conjunction with Examples 3 and 4 and Table 1, this application modifies silver powder with polypropylene glycol and limits the silver powder to dendritic silver powder and spherical silver powder, resulting in a more uniform and stable conductive network formed by the dispersion of silver powder in the system.
[0055] In conjunction with Examples 3, 5-9 and Table 1, this application limits the spherical silver powder to large and small spherical silver powders of a certain particle size, and further limits the concentration and molecular weight of the modified mixed solution of the two, so that the number and viscosity of the active groups on the surface of the large and small spherical silver powders are more suitable for the system of this application, and the distribution is more uniform and stable. By limiting the mass ratio of large and small silver powders, the silver-electric performance is better and the battery cell efficiency is higher. In conjunction with Examples 3, 10 and Table 1, the types of solvents in the system are further limited, making the silver powder more suitable for the system of this application, and the performance is further improved.
[0056] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A printing silver paste material for photovoltaic solar cells, characterized in that, The raw materials include the following parts by weight: 75-95 parts silver powder, 3-25 parts resin, 2-20 parts organic solvent, and 0.1-3 parts curing agent.
2. The photovoltaic solar cell printing silver paste material according to claim 1, characterized in that, The silver paste material also includes the following raw materials in parts by weight: 3-8 parts lead borosilicate glass, 14-16 parts aluminum oxide, 2.0-2.2 parts boron trioxide, 0.5-0.7 parts cadmium oxide, 0.1-0.3 parts calcium oxide, 0.5-0.7 parts copper oxide, 4.3-4.5 parts phosphorus pentoxide, 5.1-5.3 parts platinum oxide, 2.4-2.6 parts silicon dioxide, and 0.7-0.9 parts zinc oxide.
3. The photovoltaic solar cell printing silver paste material according to claim 2, characterized in that, The silver powder includes polypropylene glycol modified dendritic silver powder and polypropylene glycol modified spherical silver powder in a volume ratio of 1:(2.1-2.8).
4. The photovoltaic solar cell printing silver paste material according to claim 3, characterized in that, The average particle size of the dendritic silver powder is 1.0-3.0 μm, and the average particle size of the spherical silver powder is 200-800 nm.
5. The photovoltaic solar cell printing silver paste material according to claim 3, characterized in that, The nano-spherical silver powder includes small spherical silver powder with an average particle size of 200-400 nm and large spherical silver powder with an average particle size of 500-800 nm, and the volume ratio of small spherical silver powder to large spherical silver powder is 2:(1.0-1.5).
6. The photovoltaic solar cell printing silver paste material according to claim 3, characterized in that, The preparation steps of the polypropylene glycol modified spherical silver powder include: adding spherical silver powder to an ethanol-polypropylene glycol mixed solution, sonicating, filtering, and drying to obtain polypropylene glycol modified spherical silver powder.
7. The photovoltaic solar cell printing silver paste material according to claim 6, characterized in that, The mass ratio of ethanol to polypropylene glycol in the ethanol-polypropylene glycol mixed solution added to the small spherical silver powder is 1:(2.8-3.0), and the mass ratio of ethanol to polypropylene glycol in the ethanol-polypropylene glycol mixed solution added to the large spherical silver powder is 1:(2.1-2.3).
8. The photovoltaic solar cell printing silver paste material according to claim 7, characterized in that, The average molecular weight of the polypropylene glycol is 1800-2100.
9. The photovoltaic solar cell printing silver paste material according to claim 7, characterized in that, The organic solvent includes dimethyl oxalate, and the resin includes bisphenol A epoxy resin.
10. A method for preparing a printed silver paste material for photovoltaic solar cells according to any one of claims 1-9, characterized in that, Includes the following steps: Weigh the raw materials according to the weight proportions, add the resin to the organic solvent, stir at 60-85℃ until dissolved, cool and add the curing agent and mix evenly, then add the remaining components and mix evenly. Grind according to the gap between the fast roller and the medium roller: 70um and 40um, and the gap between the medium roller and the slow roller: 30um and 10um. Then degas under vacuum to obtain the silver paste material for printing photovoltaic solar cells.